Whatsapp Group Sebagai Media Komunikasi Dalam Tradisi Mapengarah Berbaris Tri Hita Karana Pada Era Revolusi Industri 4.0 - Ni Rai Vivien Pitriani (Jayapangus Press, 2020)
The writing of this article was composed to reveal the use of whatsapp groups as a medium of communication in the traditional mapengarah based teachings of Tri Hita Karana in the era of the industrial revolution 4.0. The results of this study reveal that the traditional mapengarah tradition is usually carried out to convey information from one house to another to channel important information relating to joint activities both religious activities and local traditional activities that are important to be known and carried out by the community, all of these activities based on the teachings of Tri Hita Karana and focuses on the younger generation or generation Y. Tri Hita Karana which in Hinduism teachings, it is a cause of happiness in the world, happiness starts from the existence of good and directed communication. In the era of the industrial revolution 4.0, the young generation or generation Y has been able to answer the challenges of the times by using whatsapp groups as a medium of communication in the tradition of direction, because whatsapp groups are in great demand today and how to use them easily, quickly in receiving information without having to waste a lot of time. Besides that the information accessed is right on target, in the sense that it is directly directed at the person who will be given the information.